Crustal Anisotropy Beneath the Trans-North China Orogen and its Adjacent Areas From Receiver Functions - Xu, Xiaoming; Ding, Zhifeng; Li, Li; Niu, Fenglin (Frontiers in Earth Science, 2021)
As an important segment of the North China Craton, the Trans-North China Orogen (TNCO) has experienced strong tectonic deformation and magmatic activities since the Cenozoic and is characterized by significant seismicity. To understand the mechanism of the crustal deformation and seismic hazards, we determined the crustal thickness (H), Vp/Vs ratio (κ) and crustal anisotropy (the fast polarization direction φ and splitting time τ) beneath the TNCO and its adjacent areas by analyzing receiver function data recorded by a dense seismic array. The (H, κ) and (φ, τ) at a total of 309 stations were measured, respectively. The Moho depth varies from ~30 km beneath the western margin of the Bohai bay basin to the maximum value of ~48 km beneath the northern Lüliang Mountain, which shows the positive and negative correlations with the elevation and the Bouguer anomaly. The average φ is roughly parallel to the strikes of the faults, grabens and Mountains in this study area, whereas a rotating distribution is shown around the Datong-Hannuoba volcanic regions. Based on the φ measured from the Moho Ps and SKS/SKKS phases, we propose that the crustal deformation and seismic hazards beneath the TNCO could be due to the counterclockwise rotation of the Ordos block driven by the far-field effects of the India-Eurasian collision.